ANALISIS KEPUASAN PENGGUNA JARINGAN INTERNET DI PERGURUAN TINGGI SE KOTA SURAKARTA - Huda, Khoirul; Susilo, Dahlan; Saputro Al Haris, Firdhaus Hari (Gaung Informatika, 2013)
The analysis result in college Surakarta shows that there is 42 college in evaluasi.dikti.go.id. Base on 42 colleges which are taken for sampling with confidence interval 70% , it results 9 colleges. The results of analysis shows that the user is quite satisfied with distribution scale 2.18. It is resulted from the simple linear regression model Y= 2.0617+0.0025x. The constant 2.0617 means bandwidth is also still constant with the value 2.0617. The satisfaction of Coefficient value to ward the internet user is 0.0025. It means that there is an each increasing bandwidth of internet user 1(kbps). Therefore, it causes 0.0025 satisfaction increasing value. The conclusion of this research is bandwidth capacity that less than 145 kbps categories as quite satisfied, 180-460 kbps is satisfied and more 495 kbps is very satisfied. Mikrotik and proxy are management bandwidth used in college at Surakarta